7.1 – Multiplying Monomials
x · x =
x 1 · x 1 =
x 1 · x 1 = x 2
x · x = x 2 x · x 2 =
x · x = x 2 x 1 · x 2 =
x · x = x 2 x 1 · x 2 = x 3
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ).
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)(x 2 · x 4 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)(x 2 · x 4 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)(x 2 · x 4 )(y · y 2 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)(x 2 · x 4 )(y 1 · y 2 )
x · x = x 2 x · x 2 = x 3 Ex. 1 Simplify (-7x 2 y)(4x 4 y 2 ). (-7x 2 y)(4x 4 y 2 ) (-7 · 4)(x 2 · x 4 )(y 1 · y 2 ) -28x 6 y 3
Ex. 2 Simplify (-3xy 2 z 3 ) 4
(-3xy 2 z 3 ) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x) 4 · (y 2 ) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x) 4 · (y 2 ) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x) 4 · (y 2 ) 4 · (z 3 ) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x 1 ) 4 · (y 2 ) 4 · (z 3 ) 4
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x 1 ) 4 · (y 2 ) 4 · (z 3 ) 4 81 · x 4 · y 8 · z 12
Ex. 2 Simplify (-3xy 2 z 3 ) 4 (-3xy 2 z 3 ) 4 (-3) 4 · (x 1 ) 4 · (y 2 ) 4 · (z 3 ) 4 81 · x 4 · y 8 · z 12 81x 4 y 8 z 12